ANALISIS PELAKSANAAN PEMBELAJARAN IPS PADA SISWA KELAS VII E DI SMP NEGERI 1 RASAU JAYA - Gadis Monitia; Rustiyarso Rustiyarso; Iwan Ramadhan (Universitas Tanjungpura, 2021)
AbstractThe aims of this study were to determine how the implementation of preliminary activities, core activities and closing activities of social studies learning in class VII E students Junior high school 1 Rasau Jaya. The type of research is qualitative research with descriptive research methods. The source of the data in this study was the class VII social studies teacher at Junior high school 1 Rasau Jaya. The data taken were data related to social studies learning in class VII E students at Junior high school 1 Rasau Jaya. The results of this study were (1) the implementation of the preliminary social studies learning activities for class VII E students at Junior high school 1 Rasau Jaya was quite good. This is proven by Mr. Ellisius creating conducive initial conditions and making apperceptions. (2) the core learning activities run quite well. This is evidenced by Mr. Ellisius conveying the learning objectives, using a variety of teaching materials and various strategies / methods. (3) the closing activities of the lesson went quite well. This was evidenced by Mr. Ellisius conveying to students the material to be discussed at the next meetingKeywords: Implementation of learning, Social Sciences